Book reviews.
Managing Business Processes; BPR and Beyond, by Colin Armistead and Philip Rowland. Reviewed by Mike Delany.
Educating entrepreneurs in modernising economies, edited by Peter Rosa, Michael G. Scott and Heinz Klandt. Reviewed by Slavo Radosevic.